Sikh History from Persian Sources : Translations of Major Texts - Edited by J. S. Grewal & Irfan Habib (Lahore Fiction House, 2004)
Papers presented at sixtieth session of Indian History Congress at Calicut University on December 29, 1999.
Include Index.
It is a Conference publication.
Keywords: Sikhs -- Sikhs -- History -- Congresses